ANALISIS PENGGUNAAN VARIASI MENGAJAR MATA PELAJARAN IPS TERPADU - Rusliandi, Evan; Aminuyati, Aminuyati; Budi, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract:This thesis is entitled "Analysis of the Use of Teaching Variations in Integrated Social Sciences Subjects in MTS Al-Hikmah, Tayan Hilirk District, Sanggau Regency." A common problem in this thesis is "How to Use Teaching Variations in Integrated Social Sciences Subjects in MTS Al-Hikmah, Tayan Hilir District, Sanggau District". From the results of the study, it was planned that the learning of Integrated Social Sciences subject teachers in the Planning stage was quite good. 2. The activities of Integrated Social Sciences subject teachers in the teaching process stage are quite good. The activities of Integrated Social Sciences subject teachers in the teaching process stage are quite good, this can be seen from the teacher giving questions to students about the material that has been delivered. Then conclude the results of the discussion of the subject matter discussed. In terms of assignments and assessment of Integrated Social Sciences subject teachers see the available time, if time is not possible again the assignments given to students are done at home and their assessment is carried out at the next meeting, as well as informing the subject matter to be discussed. which are available.Â Keyword : Use of Teaching Variations.